Physiological demands of match-play in elite tennis: A case study - Gomes, R. V.; Coutts, A. J.; Viveiros, L.; Aoki, M. S. (European Journal of Sport Science, 2011)
The physiological and perceptual demands together with match notation of a four-set tennis match were studied in two elite professional players during the preparation for the 2008 Davis Cup. The design of this case report is unique in that it is the first to describe the demands of prolonged match-play (197 min) over four sets in ecologically valid conditions. The variables measured before and after each set included blood lactate and glucose concentrations, body mass, and perception of effort. Stroke count for each rally and heart rate were recorded during each set while salivary cortisol concentration was determined before and after the match. The rally length decreased as the match progressed. The results showed significant physiological stress, with each player losing greater than 2.5% of body mass (as fluid) and having elevated salivary cortisol concentrations after the match. Heart rate and perception of effort were also increased following each set indicating increasing stress. However, blood lactate decreased following the fourth set while blood glucose was maintained. The results also suggest that elite players may adjust work rates or tactics to cope with the increased perception of effort. This report shows that four sets of tennis are associated with increasing stress and fatigue.